The role of soft war in the Arab spring - Ali, Hala (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Wars have many shapes and many means and there are a lot of weapons. Mind brings automatically military shape of wars when referred to. This is because of the conditional link that occurs between war and the military form. Cold war happened between Russia and USA played a role in destroying the link mentioned before. Many events followed insisted on the non-military form and non-military means of wars. This study tries to throw light on the soft means of war mostly the psychological one attempting to go over the role of Media in the events of Arabic Spring and trying to explore the dualism between image and idea and its role in breaking wars. The study tries also, through political theories, to explain how Media works on destroying Ideologies replacing them by new ideologies that serves the aims and the goals of its sponsors.